Condicionantes institucionais à execuç\~ao dos investimentos em infraestrutura econômica no Brasil: Licenciamento ambiental - Bolívar Pêgo Filho; Júlio César Roma; José Gustavo Feres; Larissa Schmidt (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– This text for discussion is part of a research aimed to understand the institutional constraints to the implementation of investment in infrastructure in contemporary Brazil and to propose public policy improvement. The rationale for their implementation is that there is evidence that indicate the low capacity of the Federal Government and Brazilian companies to perform "accelerated" investment in infrastructure projects. For analysis were selected six case studies, three successful and not successful three considered, namely: exitosos: thermoelectric of Candiota III hydroelectric power plant phase Teles Pires and BRT south exit DF; and successful not-Transnordestina, subway of Salvador and BR-163 North of Mato Grosso, Santarém (Pará). For each case study, seven conditions were analyzed: planning, designing, managing and coordinating intragovernamental; Bidding and Contracting; Socio-environmental licensing; Expropriation and land conflicts; Federal joint, State and society; Bureaucratic and judicial controls ("U"); and private protection Market of goods and services. This text, in particular, addresses the environmental licensing etching. In Brazil, through licensing, in recent years, through changes in its regulatory framework, has been a theme yet little understood and object of permanent criticism, particularly by the productive sector and linked to major economic infrastructure projects. Are cited issues such as slow decision-making and reasoning, ideological content, process and contribute to delays, increased costs, judicialization, creation of contingent liabilities and non-compliance with service delivery goals to improve the well-being of society. This text aims to make a general analysis of the problems, with the general question: what are the guiding factors and institutional conditions that interfere with the implementation of public and private investment in economic infrastructure in Brazil? Two specific questions are were defined: i) how and why the licensing relates to the ability to execute? and ii) what are the possible alternatives to improve it? Given this, some points analyzed in references and in six selected case studies help answer the question guiding general: i) the still low overall coordination capacity of MMA; ii) little articulation and cooperation between the institutions involved within and outside of Amazonia; iii) the licensing body is continually overwhelmed with questions and demands that are not necessarily of its responsibility; and iv) important intervention but sometimes excessive MPF; among others. As to the first question guiding specific, can be answered by licensing be deprecated or little considered in decision-making; by the progress of works of the projects; ideological contamination of the process; excess "developmentalism" of entrepreneurs; entrepreneurs with great economic and political power; poor quality of technical studies; among others. As for the second question guiding specific suggestions for improvements are make involving policy, regulatory, institutional issues contracts, multiplicity of actors, judicialization, etc.
Keywords: Q01; Q41; Q48; Q51; Q56; Q58; R53; R58; 330; environmental licensing; economic infrastructure; productive sector; large enterprises; environmental impact